Factors Influencing Women’s Inclination in Adopting Managerial Positions in the Nepalese Banking Sector - Shrestha, Jeshna (Nepalese Journal of Management, 2024)
The study examines the factors influencing women’s inclination in adopting managerial positions in Nepalese commercial banks. Leadership aspiration is selected as the dependent variable. The selected independent variables are financial and other benefits, support of top management personnel, social status, career role salience, perceived organizational barriers and work-family conflict. The study is based on primary data with 110 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and impact of different factors on women’s inclination in adopting managerial positions in Nepalese commercial banks. The study showed that financial and other benefits have positive impact on leadership aspiration. It indicates that better financial and other benefits lead to women’s inclination in adopting managerial positions. Similarly, support of top management personnel has a positive impact on leadership aspiration indicating that more support from top management personnel lead to women’s inclination in adopting managerial positions. Likewise, social status has a positive impact on leadership aspiration. It indicates that increase in social status leads to increase in women’s leadership aspiration. Similarly, career role salience has a positive impact on leadership aspiration. It indicates that good understanding of career role led to women’s inclination in adopting managerial positions. Moreover, perceived organizational barriers have negative impact on leadership aspiration. It shows that barriers within the organization leads to decrease in women’s inclination in adopting managerial positions. Likewise, work-family conflict has a negative impact on leadership aspiration. It indicates that lower work-family conflict led to women’s inclination in adopting managerial positions.